Simultaneous detection of multiple targets for ultrastructural immunocytochemistry - Philimonenko, V V; Philimonenko, A A; Šloufová, I; Hrubý, M; Novotný, F; Halbhuber, Z; Krivjanská, M; Nebesářová, J; Šlouf, M; Hozák, P (Histochemistry and cell biology, 2014)
Simultaneous detection of biological molecules by means of indirect immunolabeling provides valuable information about their localization in cellular compartments and their possible interactions in macromolecular complexes. While fluorescent microscopy allows for simultaneous detection of multiple antigens, the sensitive electron microscopy immunodetection is limited to only two antigens. In order to overcome this limitation, we prepared a set of novel, shape-coded metal nanoparticles readily discernible in transmission electron microscopy which can be conjugated to antibodies or other bioreactive molecules. With the use of novel nanoparticles, various combinations with commercial gold nanoparticles can be made to obtain a set for simultaneous labeling. For the first time in ultrastructural histochemistry, up to five molecular targets can be identified simultaneously. We demonstrate the usefulness of the method by mapping of the localization of nuclear lipid phosphatidylinositol-4,5-bisphosphate together with four other molecules crucial for genome function, which proves its suitability for a wide range of biomedical applications.
Keywords: protilátky; Actins; ribonukleoproteiny malé jaderné; Gold; Cell Nucleus; Cell Line, Tumor; jaderné proteiny; zlato; imunohistochemie; buněčné jádro; Phosphatidylinositol 4,5-Diphosphate; aktiny; Ribonucleoproteins, Small Nuclear; HeLa buňky; elektronová mikroskopie; proteiny buněčného cyklu; Carrier Proteins; kovové nanočástice; Nucleophosmin; Antibodies; Metal Nanoparticles; lidé; Immunohistochemistry; HeLa Cells; Humans; barvení a značení; Microscopy, Electron; fosfatidylinositol-4,5-difosfát; Staining and Labeling; nádorové buněčné linie; Cell Cycle Proteins; nukleofosmin; Nuclear Proteins; transportní proteiny